SKRINING ISSR PRIMER STUDI PENDAHULUAN KEKERABATAN ANTAR JAHE MERAH, JAHE EMPRIT DAN JAHE BESAR - Sri Wahyuni; D. H. Xu2; N. Bermawie; H. Tsunematsu; T. Ban (Buletin Penelitian Tanaman Rempah dan Obat, 2004)
Screening ISSR primer preliminary study of the relationship between small, big and red gingerScreening ISSR Primer as preliminary study the relationships of small, big and red ginger. A PCR- based method for genetic diversity analysis such as ISSR has been well developed recently. In this research, 28 ISSR primer were screened aiming to study the relationships of red, small and big ginger. Genomic DNA was isolated from rhizome using CTAB based method. The DNA were then amplified in a thermalcycler wite a total volume of 20 µl consisted of 30 – 100 ng genomic DNA, 10 pmol primer, 1x PCR buffer, 0,2 mM dNTPs, 1,5 mM MgCl2 dan 0,5 rTaq polymerase. Electroforesis of the amplification product was carried out on 1,5% agarose gel, stained with ethidium bromide and viewing on UV transiluminator light to see the banding pattern. Results showed that amplified banding pattern of ISSR range from 3 – 14. Among the 28 primers screened, 10 primers showed polymorphic banding pattern but only 3 primers showed polymorphic banas more than 25%, i. e. ISSR 18, ISSR 19, and ISSR 15 respectively. Based on the ISSR data, small and big ginger has closer relationships compared to the red ginger. To find the suitable primers that can be used to distinguished the ginger cultivar and find suitable molecular markers, more primers need to be screened.